Strategi Manajemen Kurikulum dan Metode Pembelajaran Dalam Meningkatkan Prestasi Belajar Siswa di MTs Nashirul As’adiyah Pepara Tanah Grogot - Adiyono, Adiyono; Agnia, Ana Satia; Maulidah, Tuhfah (El-Idare, 2023)
This study aims to determine curriculum strategies and learning methods in MTs Nashirul As'Adiyah Pepara in improving student achievement. This research uses a qualitative approach with data collection obtained through observation, interviews and other sources in the form of files / data. So far the curriculum management strategy process has been implemented in such a way as to implement planning, organizing, implementation and evaluation in it. By implementing several learning methods in the form of lectures, questions and answers and discussions using media to support the creation of a good learning process in the form of LCDs, teaching aids and visual media in an effort to increase achievement in students.